2017
DOI: 10.1002/glia.23231
|View full text |Cite
|
Sign up to set email alerts
|

SUR1‐TRPM4 and AQP4 form a heteromultimeric complex that amplifies ion/water osmotic coupling and drives astrocyte swelling

Abstract: Astrocyte swelling occurs after central nervous system injury and contributes to brain swelling, which can increase mortality. Mechanisms proffered to explain astrocyte swelling emphasize the importance of either aquaporin-4 (AQP4), an astrocyte water channel, or of Na 1 -permeable channels, which mediate cellular osmolyte influx. However, the spatio-temporal functional interactions between AQP4 and Na 1 -permeable channels that drive swelling are poorly understood. We hypothesized that astrocyte swelling afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 80 publications
2
117
0
Order By: Relevance
“…In an animal stroke model, SUR1 expression steadily increased up to 6 hours after the initiation of ischemia, and treatment with the sulfonylurea inhibitor glibenclamide reduced brain edema and tissue damage (Simard et al, 2006). Their most recent work demonstrated that SUR1-TRPM4 can form a tripartite complex with AQP4, and such association mediates the pathological, high-capacity influx of water that is ~7.6-fold higher than that stimulated by TRPM4 alone, and ~3.2-fold higher than that induced by the SUR1-TRPM4 assembly (Stokum et al, 2018) (Fig. 12.3E).…”
Section: A Special Case For Astrocytic Swelling and Cell Volume Controlmentioning
confidence: 98%
See 3 more Smart Citations
“…In an animal stroke model, SUR1 expression steadily increased up to 6 hours after the initiation of ischemia, and treatment with the sulfonylurea inhibitor glibenclamide reduced brain edema and tissue damage (Simard et al, 2006). Their most recent work demonstrated that SUR1-TRPM4 can form a tripartite complex with AQP4, and such association mediates the pathological, high-capacity influx of water that is ~7.6-fold higher than that stimulated by TRPM4 alone, and ~3.2-fold higher than that induced by the SUR1-TRPM4 assembly (Stokum et al, 2018) (Fig. 12.3E).…”
Section: A Special Case For Astrocytic Swelling and Cell Volume Controlmentioning
confidence: 98%
“…Perhaps, AQP4 plays more complex roles in regulating water movement and osmotic gradients, via modulating activities of ion channels and transporters. E.g., AQP4 can form functional complexes with the non-selective cation channel TRPV4 (Benfenati et al, 2011), the SUR1-TRPM4 channel complex (Stokum et al, 2018), and also regulates the activity of VRAC (Benfenati et al, 2007). …”
Section: A Special Case For Astrocytic Swelling and Cell Volume Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Supramolecular assemblies of the M23 AQP4 isoform tetramers have been reported to aggregate into orthogonal arrays and facilitate water movement [80, 92]. This pathway has reported connections with other molecular contributors to cerebral edema, including a tripartite-complex association between Sur1-Trpm4-AQP4, a glutamate uptake channel EAAT1/2, and inflammatory cytokines [79, 93, 94]. Increased intracellular water movement mediated by AQP4 channels on perivascular astrocytic foot processes contributes to cytotoxic edema.…”
Section: Molecular Pathophysiology Biomarkers and Targeted Treatmenmentioning
confidence: 99%